Premature interruption of training in Swiss 2-year apprenticeship through the lens of fit - Bosset, Isabelle; Hofmann, Claudia; Duc, Barbara; Lamamra, Nadia; Krauss, Annette (Swiss Journal of Educational Research, 2022)
This contribution examines premature interruption of training (PIT) through the lens of fit between the training and the trainees. To do so, it explores early indicators of PIT and the reasons cited by young people for training interruption. Using quantitative and qualitative approaches, 628 questionnaires were handed out, and 31 semi-structured interviews were conducted. All participants were enrolled in the 2-year apprenticeship leading to a Federal Vocational Education and Training (VET) Certificate, a low-threshold training track in the Swiss VET system. The findings reveal which elements are involved in poor fit and how they may contribute to PIT.